Newsletter for Europe: No.41, October 2010 - Bioversity International (2010)
Bioversity's Regional Office for Europe provides the Coordination Secretariats for the European Cooperative Programme for Plant Genetic Resources (ECPGR) and for the European Forest Genetic Resources Programme (EUFORGEN). Bioversity publishes regular issues of the Newsletter for Europe throughout the year. This Newsletter is intended to serve as an informal forum for the exchange of news and views, and to create closer ties within the genetic resources community in Europe.